Natural Product and Health - A Review on All Aspects - Gopal Kumar; Yashwant Kumar Singh; Pranav Prabhat; Md. Rahmat Ali; Mrityunjay Kumar (Current Research in Pharmaceutical Sciences, 2013)
India is the largest producer of medicinal herb and is called as Botanical garden of the World. During the thousands of years of early human existence many natural material were identified for combating human ailments either by instinct or intuition or trial and error. India is one of the world’s 12 leading biodiversity centers. It is endowed with more than 47,000 known species of plants. Out of these, about 20,000 plants have good medicinal value. According to the WHO survey 80% of the populations living in the developing countries rely almost exclusively on traditional medicine for their primary health care needs.The global market for herbal medicines currently stands at over $60 billion annually. Medicinal plants play a great role in food supplements for care as well as in personal care of the mankind alongside the therapeutically active substances, thus medicinal plant based industry is a promising sector and enormous economic growth potential. Nutraceuticals (Health Food) are in great demand in the developed world.